2020
DOI: 10.1002/bdr2.1793
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of maternal exposure to fungicides on behavioral development in F1‐generation mice: 2. Fixed‐dose study of thiabendazole

Abstract: Background: Few published studies are reported for the neurobehavioral toxicity of combined exposure to fungicides in mammals. This study was aimed to re-evaluate the reproductive and neurobehavioral effects of maternal exposure to combined imazalil (IMZ) and thiabendazole (TBZ) with fixed-dose of TBZ in mice. Methods: IMZ/TBZ were given in the diet to provide levels of 0%/0% (control), 0.0015%/0.018% (IMZ/TBZ), 0.006%/0.018% and 0.024%/0.018% during the gestation and lactation periods. Selected reproductive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These results suggest that the high‐dose levels (HH) of IMZ/TBZ in the first study (Study I: Tanaka et al, 2020a) influenced strongly the exploratory and spontaneous behavior in adult mice finishing chemical administration than high‐dose levels (HM and MH, respectively) of IMZ/TBZ in the second (Study II: Tanaka et al, 2020b) and present (Study III) studies. The presumed level of high‐dose TBZ in the second study (26–74 mg kg −1 bw day −1 ) was lower than in the first study (87–215 mg kg −1 bw day −1 ) and that of IMZ was similar in both studies (2.2–98 mg kg −1 bw day −1 and 2.3–96 mg kg −1 bw day −1 , respectively).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…These results suggest that the high‐dose levels (HH) of IMZ/TBZ in the first study (Study I: Tanaka et al, 2020a) influenced strongly the exploratory and spontaneous behavior in adult mice finishing chemical administration than high‐dose levels (HM and MH, respectively) of IMZ/TBZ in the second (Study II: Tanaka et al, 2020b) and present (Study III) studies. The presumed level of high‐dose TBZ in the second study (26–74 mg kg −1 bw day −1 ) was lower than in the first study (87–215 mg kg −1 bw day −1 ) and that of IMZ was similar in both studies (2.2–98 mg kg −1 bw day −1 and 2.3–96 mg kg −1 bw day −1 , respectively).…”
Section: Discussionmentioning
confidence: 67%
“…Tanaka et al (2020b) reported that the average speed significantly slowed through 120 min in the high‐dose group (HM) of IMZ/TBZ (maternal exposure to approximately 35–98 and 26–74 mg kg −1 bw day −1 , respectively) in adult males, and the average time of rearing lengthened significantly through 120 min in the high‐dose group (HM) of females (Study II). The longitudinal pattern of the average time of rearing showed a similar but quantitative difference between the control and IMZ/TBZ treatment groups in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on pesticides as target pollutants, the neonicotinoid insecticide acetamiprid (ACT) and the azole fungicide thiabendazole (TBZ) are very common substances, frequently used on Spanish and Greek fruit crops. Even if ACT and TBZ are allowed from the EU legislations without restrictions [ 11 , 12 , 13 ], many studies claim that they are suspicious for toxicity effects on mammals, bacteria, or fish after chronic exposure or in combination with other pesticides [ 14 , 15 , 16 , 17 ]. For this reason, the efficient agro-industrial wastewater treatment, the complete elimination of these pesticides and the safe disposal of the effluents is of great importance, in order to avoid any environmental threat.…”
Section: Introductionmentioning
confidence: 99%